Fundamental niche prediction of the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii in Europe - ÇERİKÇİOĞLU, NİLGÜN (WILEY, 2017)
Fundamental niche prediction of Cryptococcus neoformans and Cryptococcus gattii in Europe is an important tool to understand where these pathogenic yeasts have a high probability to survive in the environment and therefore to identify the areas with high risk of infection. In this study, occurrence data for C. neoformans and C. gattii were compared by MaxEnt software with several bioclimatic conditions as well as with soil characteristics and land use. The results showed that C. gattii distribution can be predicted with high probability along the Mediterranean coast. The analysis of variables showed that its distribution is limited by low temperatures during the coldest season, and by heavy precipitations in the driest season. C. neoformans var. grubii is able to colonize the same areas of C. gattii but is more tolerant to cold winter temperatures and summer precipitations. In contrast, the C. neoformans var. neoformans map was completely different. The best conditions for its survival were displayed in sub-continental areas and not along the Mediterranean coasts. In conclusion, we produced for the first time detailed prediction maps of the species and varieties of the C. neoformans and C. gattii species complex in Europe and Mediterranean area.
Keywords: SPECIES COMPLEX; VAR. GATTII; SEROTYPE-D; INFECTION; ENVIRONMENT; COLOMBIA; CLIMATE; BOGOTA; IMPACT; TREES